Activity Test of 96% Ethanol Extract of Water Guava Leaf (Syzygium aqueum) on LDL and HDL Values with Propylthiouracil Induction in Rats - Siti Setianingsih; Sunarti; Muhammad Maulana (LPPM Universitas Harapan Bangsa, 2024)
One of the plants that can be thought to have antihyperlipidemic potential is water guava leaves (Syzygium aqueum) because they contain chemical compounds, one of which is flavonoids. The aim of this research is to determine the activity of 96% ethanol extract of water guava leaves (EEDJA) as an antihyperlipidemic agent. Male Wistar rats were induced using propylthiouracil (PTU) for 2 weeks (14 days). Hyperlipidemic mice were divided into 5 test groups, CMC-Na group, simvastatin group, EEDJA group (100, 200 and 400) mg/BW. The solution was given to mice routinely once a day for 2 weeks (14 days) orally. The results of the study showed that there were differences before and after administration of EEDJA (100, 200 and 400) mg/BW in LDL and HDL levels with a significance value of 0.000 (<0.005). The conclusion from this study is that EEDJA has potential as an antihyperlipidemic agent in male white Wistar rats